Goethe e Brecht em diálogo - Heise, Eloá (In:Pandaemonium Germanicum;São Paulo : Departamento de Letras Modernas, Faculdade de Filosofia, Letras e Ciências Humanas, Universidade de São Paulo, 1997-;Band 12 (2008), Seite 14-22;Online-Ressource, 2008)
The purpose of this paper is to compare two prologs, namely 'Prolog im Himmel' in
urn:nbn:de:hebis:30:3-261332
Keywords: Online-Publikation; Brecht; Bertolt; Goethe; Johann Wolfgang von; Der gute Mensch von Sezuan; Faust; Intertextualität; Parodie